Combined Administration of Streptozotocin and Sucrose Accelerates the Appearance of Type 2 Diabetes Symptoms in Rats - Martha Isela Barragán-Bonilla; Juan Miguel Mendoza-Bello; Penélope Aguilera; Isela Parra-Rojas; Berenice Illades-Aguiar; Mónica Ramírez; Mónica Espinoza-Rojo (Journal of Diabetes Research)
Type 2 diabetes is a disease with a high global prevalence, characterized by chronic hyperglycemia, insulin resistance, polyphagia, polydipsia, polyuria, and changes in body weight. Animal models have been very useful for the study of this disease and to search for new therapeutic targets that delay, attenuate, or avoid diabetic complications. The purpose of this work was to establish a model of type 2 diabetes and exhibit the majority of the characteristics of the disease. Two-day-old male and female Wistar rats were treated once with streptozotocin (70 or 90 mg/kg body weight). After weaning, they were given a sucrose-sweetened beverage (SSB; sucrose at 10 or 30%) during 7 or 11 weeks; their body weight and food intake were measured daily. With the rats at 14 weeks of age, we determined the following: (a) fasting blood glucose, (b) oral glucose tolerance, and (c) insulin tolerance. We found that the supplementation of sucrose at 10% for 7 weeks in male rats which had previously been given streptozotocin (70 mg/kg) at neonatal stage leads to the appearance of the signs and symptoms of the characteristic of type 2 diabetes in adulthood.